‘Life is more important than money’: ransom mobilization and delivery to kidnappers in Northeast Nigeria - Oludayo, Tade (Deviant behavior, 2023)
Despite growing research on kidnapping in Nigeria, little is known about how families mobilize resources and deliver ransom to kidnappers. Information in this regard is important to appreciate the experiences, challenges, and coping strategies of those with family members who have been kidnapped. Using exploratory design and in-depth interviews, data were elicited from released kidnapped victims, two women whose husbands had been kidnapped, ransom negotiators and deliverers, and security agents in Adamawa, northeast Nigeria. Findings showed ransom negotiators were either nominated by families or by the person kidnapped. Kidnappers used threat and beating of their captives to unsettle families and pressure them to raise ransoms. Family members raised ransoms through family, church and community donations, and through loans. Wives of kidnapped persons coped with spiritual support from church, experiences of others who faced similar situation, and counseling from Significant others.